Dysfunkcje współczesnej rodziny z perspektywy statystyki sądowej - Kowalczyk, Danuta (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The problems connected with the dysfunctions of the contemporary family are the subject of the study. Judicial statistics related mostly to the proceedings of family courts have been employed in the analysis. Emphasis has been placed on the problems related to the marital bond and parental responsibility. Statistical data suggests that there are some negative phenomena in both of these realms. Divorce and separation still constitute the cause of the incompleteness of family environments. The level of court interference in how parental responsibility is exercised which serves to protect children from the hazards of the lack of proper care is still not decreased.
Keywords: family; family court; dysfunctions; marital bond; parental responsibility